2022
DOI: 10.3390/antibiotics11091263
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Mechanisms of Resistance and Treatment Algorithm for Infections Due to Carbapenem-Resistant Gram-Negative Bacteria: An Expert Panel Opinion

Abstract: Antimicrobial resistance represents a serious threat for global health, causing an unacceptable burden in terms of morbidity, mortality and healthcare costs. In particular, in 2017, carbapenem-resistant organisms were listed by the WHO among the group of pathogens for which novel treatment strategies are urgently needed. Fortunately, several drugs and combinations have been introduced in recent years to treat multi-drug-resistant (MDR) bacteria. However, a correct use of these molecules is needed to preserve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 182 publications
0
9
0
Order By: Relevance
“…The emergence of AMR is limiting the use of the traditional drugs active against A.baumannii infections, including colistin [6]. The recent development of novel agents, including cefiderocol, is a promising resource against CRAB infections, but data on its efficacy in this setting is limited and contrasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of AMR is limiting the use of the traditional drugs active against A.baumannii infections, including colistin [6]. The recent development of novel agents, including cefiderocol, is a promising resource against CRAB infections, but data on its efficacy in this setting is limited and contrasting.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its difficult-to-treat resistance phenotype and the increased mortality rate compared with carbapenem-susceptible A. baumannii infections [5,6], the preferred treatment for carbapenem-resistant A. baumannii (CRAB) infections is still controversial [7]. The recent development of novel agents such as cefiderocol, a siderophore cephalosporin with a large spectrum of resistance towards most betalactamases, could expand the armamentarium against CRAB infections.…”
Section: Introductionmentioning
confidence: 99%
“…S. maltophilia and E. anophelis are both considered MDROs because of their intrinsic resistance to multiple classes of antibiotics, including penicillin, cephalosporins, macrolides, aminoglycosides, FQs, and carbapenems [81,82]. The molecular mechanisms of antimicrobial resistance in S. maltophilia include chromosomal ß-lactamases ( bla L1 and/or bla L2 ), class 1 intergrons and ISCR elements, multiple efflux pumps, Sm qnr , antibiotic-modifying enzymes, phosphoglucomutase, mutations of topoisomerase and gyrase genes, and a reduction in outer membrane permeability [83,84–86]. For E. anophelis , several antimicrobial resistance genes, including bla B , bla GOB , bla CME , Sul2 , erm(F) , GyrA , Tet(X) , and catB, were identified in genomic analysis and were associated with ß-lactam, trimethoprim/sulfamethoxazole, macrolide, quinolone, and chloramphenicol resistance [87–90,91 ▪ ,92].…”
Section: Treatment Of Stenotrophomonas Maltophilia and Elizabethkingi...mentioning
confidence: 99%
“…Over the last decade, CPO have spread throughout the world and are now endemic in healthcare facilities in numerous countries. 1,2 CPO are being frequently encountered in hospitals and pose a significant challenge in clinical practice due to their resistance to many or all antibiotics in clinical use. Clinical outcome studies into infections caused by CPO have shown mortality rates to be as high as 40%.…”
Section: Introductionmentioning
confidence: 99%